Delirium: Prevalence and outcome in the very old in 27 medical departments during a one-year prospective study. Issue 6 (December 2022) - Marquetand, Justus; Bode, Leonie; Fuchs, Simon; Ernst, Jutta; von Känel, Roland; Boettger, Soenke
Abstract: Objective: The prevalence and effects of delirium in very old individuals aged ≥80 years have not yet been systematically evaluated. Therefore, this large single-center study of the one-year prevalence of delirium in 3, 076 patients in 27 medical departments of the University Hospital of Zurich was conducted. Methods: Patient scores on the Delirium Observation Screening scale, Intensive Care Delirium Screening Checklist, Diagnostic and Statistical Manual, 5th edition, and electronic Patient Assessment–Acute Care (nursing tool) resulted in the inclusion of 3, 076 individuals in 27 departments. The prevalence rates were determined by simple logistic regressions, odds ratios (ORs), and confidence intervals. Results: Of the 3, 076 patients, 1, 285 (41.8%) developed delirium. The prevalence rates in the 27 departments ranged from 15% in rheumatology (OR = 0.30) to 73% in intensive care (OR = 5.25). Delirious patients were more likely to have been admitted from long-term care facilities (OR = 2.26) or because of emergencies (OR = 2.24). The length of their hospital stay was twice as long as that for other patients. Some died before discharge (OR = 24.88), and others were discharged to nursing homes (OR = 2.96) or assisted living facilities (OR = 2.2). Conclusion: This is the largest study to date regarding the prevalence of delirium in patients aged ≥80 years and the medical characteristics of these patients. Almost two out of five patients developed delirium, with a high risk of loss of independence and mortality.